Management of delivery dates of aircraft spare parts and components to maintenance and repair center - S. A. Kropiventseva (Научный вестник МГТУ ГА)
The problem of foreign-made spare parts and components import delivery is relevant because international cooperation in aviation industry has become widespread. Logistics provides not only new components procurement but also borrowing, renting, leasing or exchange operations. To control the process effectively, it is necessary to decompose the import delivery process, as effective integrated logistics provides spare parts and components delivery within the shortest time and the lowest costs. Project management methods are used for this purpose. The object of the research is import delivery of foreign-made spare parts and components to maintenance and repair center. For the shortest delivery time and the lowest delivery costs it is necessary to describe the import delivery structure, to determine the import delivery works interrelations and their duration and to standardize implementation costs. The research describes the foreign-made spare parts and components import delivery structure, explains the operations sequence, sets the approximate work duration. The import delivery network schedule was also made. Implementation of the resulting structure in project management software will allow to control import delivery time and costs, to make out reports on resource usage. The import delivery project passport will help to manage the resources costs, used for spare parts and components delivery as well as to optimize the project.